Konsep diri dan kedisiplinan belajar siswa - Niko Reski; Taufik Taufik; Ifdil Ifdil (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2017)
Self- consept is one of the factors that affect student learning in school discipline. Positive self-concept, is essential for students to direct their behavior in accordance with the discipline learned in school. This study is a comparative descriptive study aims to identify and discipline konsepdiri students learn discipline and lack of discipline of learning, and to identify the concept of self-discipline and less disciplined students learn. results showed that the concept of self-discipline and less disciplined students are in good enough category and discipline students learn discipline and lack of discipline in the category quite well and there are significant differences between students learn discipline and lack of discipline. disperlukan potimalisasi role of all the schools umtuk improve self-concept and discipline of student learning.